Infrared spectroscopy as a tool to characterise starch ordered structure—a joint FTIR–ATR, NMR, XRD and DSC study - Warren, Frederick J.; Gidley, Michael J.; Flanagan, Bernadine M. (Carbohydrate polymers, 2016)
•A larger sample set (61) of starches than has been used in previous studies.•Full structural characterisation using a range of techniques.•A non-linear, hydration dependent response occurs in the infrared spectrum.•Complex changes in the infrared spectra of starch with increasing structural order. Starch has a heterogeneous, semi-crystalline granular structure and the degree of ordered structure can affect its behaviour in foods and bioplastics. A range of methodologies are employed to study starch structure; differential scanning calorimetry, 13C nuclear magnetic resonance, X-ray diffraction and Fourier transform infrared spectroscopy (FTIR). Despite the appeal of FTIR as a rapid, non-destructive methodology, there is currently no systematically defined quantitative relationship between FTIR spectral features and other starch structural measures. Here, we subject 61 starch samples to structural analysis, and systematically correlate FTIR spectra with other measures of starch structure. A hydration dependent peak position shift in the FTIR spectra of starch is observed, resulting from increased molecular order, but with complex, non-linear behaviour. We demonstrate that FTIR is a tool that can quantitatively probe short range interactions in starch structure. However, the assumptions of linear relationships between starch ordered structure and peak ratios are overly simplistic.